STUDENT LOYALTY IN PRIVATE HIGHER EDUCATION: SERVICE QUALITY AND INSTITUTIONAL IMAGE - Patwayati Patwayati; Abdul Latif; Adwi Adwi (Journal of Information Systems Management and Digital Business, 2026)
This study examines the effects of educational service quality and institutional image on student loyalty, with perceived value positioned as a moderating variable, in private higher education institutions in Kendari City, Indonesia. Drawing on service marketing and relationship marketing perspectives, this study argues that student loyalty is shaped not only by functional service experiences but also by reputational and value-based evaluations. A quantitative cross-sectional survey was conducted involving 70 students from private higher education institutions. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The findings reveal that educational service quality has the strongest positive effect on student loyalty, indicating the importance of reliable academic services, lecturer competence, administrative responsiveness, learning facilities, and digital academic support. Institutional image also positively influences student loyalty, suggesting that reputation, credibility, graduate image, and academic image are strategic assets for private higher education institutions. Perceived value contributes to student loyalty, although its moderating role requires cautious interpretation. The study contributes to higher education service marketing by positioning student loyalty as a relational outcome shaped by service quality, institutional image, and perceived value. Practically, private higher education institutions should strengthen service responsiveness, institutional credibility, and value-based student experiences to enhance loyalty.